2006
DOI: 10.1159/000098195
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulodexide on Albuminuria, NAG Excretion and Glomerular Filtration Response to Dopamine in Diabetic Patients

Abstract: Background: Albuminuria is the best and most readily available marker for glomerular damage and progressive renal function loss in patients with diabetic nephropathy. Recently, administration of the oral glycosaminoglycan sulodexide (a mixture of 80% fast-moving heparin and 20% dermatan sulphate) was shown to effectively decrease albumin excretion rate in diabetics with nephropathy. Aims: To evaluate whether the hypoalbuminuric effect of sulodexide is associated with improvement of the renal vascular or tubule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
(30 reference statements)
0
14
1
Order By: Relevance
“…57 In addition, sulodexide treatment has been shown to improve albuminuria in patients with types 1 and 2 diabetes in several small studies. [58][59][60] Various mechanisms that could be responsible for an increase in ESL volume and a decrease in albuminuria have been described. [61][62][63][64] For instance, it has been shown that sulodexide increases synthesis and sulfation of heparan sulfates.…”
Section: Esl Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…57 In addition, sulodexide treatment has been shown to improve albuminuria in patients with types 1 and 2 diabetes in several small studies. [58][59][60] Various mechanisms that could be responsible for an increase in ESL volume and a decrease in albuminuria have been described. [61][62][63][64] For instance, it has been shown that sulodexide increases synthesis and sulfation of heparan sulfates.…”
Section: Esl Modulationmentioning
confidence: 99%
“…Not all trials investigating long-term sulodexide administration reported BP values or BP reduction, and none of the studies were designed to specifically examine the effect of sulodexide on BP. 59,[66][67][68] Moreover, BP was already on target when sulodexide was added in most of the studies, and antihypertensive drugs were not actively controlled. 58,[66][67][68] Because the largest BP-lowering effect (mean placebo-subtracted BP reduction=214.6/28.3 mmHg) was observed in a crossover study in patients with diabetes and uncontrolled hypertension, sulodexide may especially lower BP in patients with hypertension and expanded ECV.…”
Section: Esl Modulationmentioning
confidence: 99%
“…13,[15][16][17]21 One used enoxaparin while the remaining four involved sulodexide. Gambaro et al, utilized three different sulodexide doses and was treated as three separate treatment arms (a, b, c).…”
Section: Effects Of Heparinoid Supplementation On Albuminuriamentioning
confidence: 99%
“…8,[14][15][16][17][19][20][21][22] Three expressed the results in terms of SCr (Figure 4) while four expressed the results in terms of CrCl ( Figure 5). The inverse variance method was used since the variables were continuous.…”
Section: Effect Of Heparinoid Supplementation On Azotemiamentioning
confidence: 99%
See 1 more Smart Citation